EBSD study to analyse mechanisms of phase boundary and grain boundary development in WC-Co cemented carbides. (27th May 2017) - Pellan, Maxime; Lay, Sabine; Missiaen, Jean-Michel; Norgren, Susanne; Angseryd, Jenny; Coronel, Ernesto; Persson, Tomas
ABSTRACT: A systematic characterisation of the boundary structure in WC-Co cemented carbides was made as a function of the cobalt content and carbon potential using electron backscattered diffraction technique, with the aim to analyse the mechanisms of WC/Co phase boundary and WC/WC grain boundary development. The fraction of grain boundaries with basal or prismatic habit planes was estimated using a stereological method. Special grain boundaries were classified as a function of the rotation axis between adjacent grains. Although a few special grain boundaries originate from the powder, most grain boundaries form during heat treatment. The development of grain boundaries and phase boundaries during sintering is discussed from the results. The surprising lack of variation in the distribution of boundary types over large changes in volume fraction and composition is particularly commented. Finally, a mechanism of cooperative migration of grain boundaries and phase boundaries is proposed to explain microstructural observations associated with grain growth.